2022
DOI: 10.21203/rs.3.rs-1364609/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

JQ1 attenuates neuroinflammation by inhibiting the inflammasome-dependent canonical pyroptosis pathway in SAE

Abstract: Sepsis-associated encephalopathy (SAE) manifests clinically in hyperneuroinflammation. Pyroptosis, which can induce an inflammatory cascade response, has been considered to be a causative factor of SAE. Evidence has shown that the bromo- and extraterminal (BET) proteins (including BRD2, BRD3, BRD4 and BRDT) inhibitor JQ1 can inhibit inflammation and suppress pyroptosis in various diseases. Therefore, we examined the effect of JQ1 on inflammasome-induced pyroptosis in the hippocampus in a mouse model of sepsis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
0
0
0
Order By: Relevance
“…Preemptive administration of IL-1 receptor antagonist (IL-1Ra) significantly reduced plasma cytokines and hippocampal microgliosis and ameliorated cognitive dysfunction, which suggested that blocking IL-1 signaling attenuated the inflammatory cascade in response to LPS, thereby reducing microglial activation and preventing behavioral abnormalities [62]. Metformin can partially reverse the severe prognosis caused by sepsis by blocking microglial proliferation and inhibiting the production of inflammatory factors [72]. Cortistatin-14 is a neuropeptide structurally resembling somastostatin, which relieves anxiety-related behaviors in CLP mice, decreases the levels of various inflammatory cytokines, reduces sepsis-induced BBB disruption, and inhibits microglial activation [70].…”
Section: Blockers Of Inflammatory Factors and Pyroptosismentioning
confidence: 99%
“…Preemptive administration of IL-1 receptor antagonist (IL-1Ra) significantly reduced plasma cytokines and hippocampal microgliosis and ameliorated cognitive dysfunction, which suggested that blocking IL-1 signaling attenuated the inflammatory cascade in response to LPS, thereby reducing microglial activation and preventing behavioral abnormalities [62]. Metformin can partially reverse the severe prognosis caused by sepsis by blocking microglial proliferation and inhibiting the production of inflammatory factors [72]. Cortistatin-14 is a neuropeptide structurally resembling somastostatin, which relieves anxiety-related behaviors in CLP mice, decreases the levels of various inflammatory cytokines, reduces sepsis-induced BBB disruption, and inhibits microglial activation [70].…”
Section: Blockers Of Inflammatory Factors and Pyroptosismentioning
confidence: 99%